Application of Active Cycle of Breathing Technique in Post-Tuberculosis Obstruction Syndrome Patients - Anggi Jamiyanti; Lintang Tiara Hanandita; Tuti Suprapti (Jurnal Keperawatan Profesional, 2026)
Patients with post-tuberculosis obstructive syndrome (PTOS) often experience ineffective airway clearance due to residual lung tissue damage. This study aimed to evaluate the application of the Active Cycle of Breathing Technique (ACBT) in two PTOS patients with ineffective airway clearance and to observe its impact on sputum production and dyspnea reduction. A qualitative case study design was conducted in a pulmonary ward in January 2025. Informed consent was obtained from both patients prior to participation. Data were collected through semi-structured interviews, direct daily observation, physical examination, and medical record review. Observed parameters included respiratory rate, oxygen saturation, breath sounds, cough effectiveness, sputum volume, and perceived dyspnea. ACBT was performed for three consecutive days, 3–4 sessions per day. Results showed a decrease in respiratory rate in Patient 1 from 26 to 20 breaths/min and an increase in SpO₂ from 95% to 98%. Patient 2 maintained a stable rate of 22 breaths/min with SpO₂ increasing from 97% to 98%. Both patients demonstrated increased sputum expectoration, improved cough effectiveness, and reduced dyspnea symptoms. ACBT proved to be an effective nursing intervention for managing airway clearance in PTOS patients. The development of standard operating procedures (SOPs) and further quantitative research with larger samples and long-term follow-up is recommended.